How political illusions harm national security: fiscal illusion as a source of taxation - Mourão, Paulo (2013)
Fiscal illusion is the most common form of political illusions. This article introduces an agent-based model developed for testing the Fasiani model of fiscal illusion. The Fasiani model introduces fiscal illusion as a source of extra taxation that can lead to an impoverishment of citizens and to null national production after a several periods of increasing levels of fiscal illusion. We modeled this strategy as a “dictator game,” in which we show that a state that constantly deceives its citizens is a source of national instability, deeply harming its national security